Use of Total Organic Carbon Analyzer in Isotherm Measurements of Co-Adsorption of VOCs and Water Vapor from the Air - Dragana Kešelj; Dragica Lazić; Zoran Petrović (Acta Chimica Slovenica, 2022)
The binary adsorption isotherms of volatile organic compounds (VOCs), and water vapor from the air have been the focus of much research in recent years. The content of adsorbed VOCs in the presence of water vapor can be determined by the volumetric or gravimetric method, in a static or dynamic mode. This study focuses on the adsorption technique in a static mode for isotherm measurement of the co-adsorption of VOCs and water vapor from the air using the gravimetric method. The content of VOCs is determined using a total organic carbon analyzer, while the amount of the adsorbed water was calculated from the difference between total adsorption (VOCs and water) and the adsorbed VOCs. This paper presents several adsorption isotherms with different VOCs (toluene, benzene, methanol, ethanol and isopropyl alcohol) and adsorbents (ZSM-5 zeolite, silica gel and Na-Form mordernite) in the presence of water vapor. The well-known adsorption isotherm models (Langmuir, extended Langmuir, Freundlich, extended Freundlich and Hill) were used to treat experimental results. The adjusted R-Squared (adj. R2)  values obtained for those non-linear models for isotherms (total adsorpton (qe,tot) as a function of equilibrium concentration of VOC (Ce) and the adsorbed VOC (qe) as a function of equilibrium concentration of VOC (Ce) are used to determine the best-fit isotherm model. The modeling results showed that the 3-parameter models could fit the data better than the 2-parameter model, with relatively higher adj. R2. Experimental results demonstrate that the presented adsorption technique can be used for isotherm measurement of the co-adsorption of VOCs and water vapor from the air.